BOOK REVIEW: KOREA REBORN: A MODEL FOR DEVELOPMENT (Margalla Papers, 2023)
Korea has had a turbulent and challenging history since 1945. The brutal dismemberment of the country quickly diminished the joy of being freed from Japan’s colonial rule. However, these difficulties did not go in vain. Despite a cloudy and hopeless future, determination and hope emerged from suffering. This book results from random observations and notes taken by the author, Park Chang Hee, an Army General and politician who led South Kora from 1961 to 1979. It traces the journey of the Korean nation from trials and tribulations to regeneration and modernization through five chapters, included as introductory section titled “On the Threshold of a New History” and the conclusion titled “Korea’s Path to Regeneration.” Bibliography EntryKhan, Ajab. 2023. "Korea Reborn: A Model for Development." Margalla Papers 27 (2): 125-128.